2006
DOI: 10.1542/peds.2005-2271
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Wheeze in Early Childhood and Asthma Among Children at Risk for Atopy

Abstract: The absence of recurrent early wheeze indicates a very low risk of asthma at school age among children with parental history of asthma or allergies. Early identification of children who will develop asthma at school age is difficult, even in children at risk for atopy. However, children with parental history of asthma or allergies who have frequent early wheeze, in particular, are at greatly increased risk of asthma and merit close clinical follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 18 publications
1
58
1
5
Order By: Relevance
“…10 As such, this finding may have relevance to racial health disparities in rates of early childhood wheezing, which remains a prevalent problem with high rates of morbidity. 42 This study has the following limitations. First, selfreported BMI is affected by a well-established systematic underreporting of weight by up to 5 pounds.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…10 As such, this finding may have relevance to racial health disparities in rates of early childhood wheezing, which remains a prevalent problem with high rates of morbidity. 42 This study has the following limitations. First, selfreported BMI is affected by a well-established systematic underreporting of weight by up to 5 pounds.…”
Section: Discussionmentioning
confidence: 96%
“…This reinforces the need to follow this population over time to determine if maternal BMI is associated with asthma (not just early childhood recurrent wheeze) similar to the findings of the Dutch study by Scholtens et al 3 However, recurrent wheezing is an important endpoint given the level of morbidity in inner-city populations during early childhood. 42 Third, there are other potential unmeasured confounders, including weight gain during pregnancy, exposure to paternal smoking (if the father lives in another residence), postnatal child diet, and prenatal maternal diet, 44,45 which may influence levels of immuno-modulatory factors such as vitamin D or folate. [46][47][48][49] However, some studies of these potential confounding factors such as prenatal maternal diet have not found associations with infant wheezing or asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Episódios recorrentes de sibilância podem estar associados a maior risco de desenvolvimento de asma [1][2][3][4][5] . Ly et al 11 , no acompanhamento de uma coorte até os 7 anos, concluíram que crianças com história de pais com asma ou alergia que têm sibilância recorrente precoce, definida como ≥ dois relatos de sibilância por ano nos primeiros 3 anos de vida, têm um risco significativamente aumentado para asma e merecem um acompanhamento clínico. Na análise dos fatores associados ao uso de corticoide para sibilância no primeiro ano de vida, observou-se que as crianças com maior morbidade tiveram maior chance de receber uma prescrição de CO e CI.…”
Section: Discussionunclassified
“…Também foi demonstrada relação entre sibilância precoce e sensibilização precoce a alimentos ou aeroalér-genos, função pulmonar reduzida e nível sanguí-neo elevado de eosinófilos, com posterior persistência destes sintomas 3,14 . Porém, nenhum desses fatores, genéticos ou ambientais, quer façam parte da anamnese, do exame físico ou de meios complementares de diagnóstico, apresentou poder suficiente para ser usado como marcador único na identificação de asma no futuro.…”
Section: Introductionunclassified
“…Porém, nenhum desses fatores, genéticos ou ambientais, quer façam parte da anamnese, do exame físico ou de meios complementares de diagnóstico, apresentou poder suficiente para ser usado como marcador único na identificação de asma no futuro. Apesar disso, poucos são os estudos que avaliam fatores de risco para sibilância em crianças no primeiro ano de vida 14,15 .…”
Section: Introductionunclassified